Amino‐Terminated Hyperbranched Polymer‐Based Recyclable Elastic Fibers for a Breathable and Antibacterial Triboelectric Nanogenerator. Issue 9 (5th June 2022) - Jia, Pan; Wang, Li; Yao, Xuefeng; Zhang, Desuo; Lin, Hong; Li, Yi; Chen, Yuyue; Xiong, Jiaqing
Abstract: Realizing recyclable triboelectric active materials with commendable elasticity, breathability, and durable antibacterial performance is significant for the sustainable development of wearables and bioelectronics. A spinnable elastic polymer (MPVA) is developed by modifying polyvinyl alcohol (PVA) with amino‐terminated hyperbranched polymers (HBP‐NH2 ), demonstrating a junction‐reinforced electrospun nanofiber membrane (MPVA) with lower Young's modulus and improved stretchability, which exhibits robust network structure and tunable air permeability to sustain 50 tensile cycles at 50% strain. Trapped silver nanoparticles (Ag NPs) in the fibers reduced in situ by the terminal groups of HBP‐NH2 demonstrate MPVA/Ag NPs nanofiber membrane with reliable antibacterial capability for both E. coli and S. aureus . By spraying a silver nanowires (Ag NWs) electrode on the antibacterial fiber membrane to serve as a single‐electrode stretchable (≈50% strain) triboelectric nanogenerator (TENG), it is demonstrated that stable triboelectric output can be maintained regardless of resistance change (Δ R / R 0 ) within 50%. Self‐powered identification of contacting objects is demonstrated. The antibacterial breathable fiber membrane can be facilely dissolved in water for regeneration via electrospinning, which is promising for sustainable development of future transient TENGs and bioelectronics. Abstract : An elastic nanofiber membrane with breathability and antibacterial capability is developed as a wearable sensor and triboelectric active material, which can be quickly dissolved in water and facilely recycled for regeneration of antibacterial nanofiber membrane. It proposes a strategy of multifunctional fiber materials for long‐term on‐skin application, which is promising for sustainable development of future transient wearables and self‐powered bioelectronics.